1980
DOI: 10.3758/bf03209739
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing the occurrence or nonoccurrence of interim drinking

Abstract: Four pairs of rats were studied in a yoked control design intended to determine if an interim activity (schedule-induced drinking) was sensitive to operant contingencies. Food was always presented on a fixed-time 30-sec schedule. Additionally, a positive or negative operant contingency was in effect during the first 6 sec of each interval. The positive (drink/food) contingency produced an extra food presentation at the 6th second of an interval if the lead rat drank at least once in the first 6 sec. The negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
(15 reference statements)
1
7
0
Order By: Relevance
“…The operant contingency helped to develop scheduleinduced drinking under environmental conditions (food frequency) that, by themselves, did not induce that much licking, and the degree of contingency established between licking and food delivery determined the level of acquisition of scheduleinduced drinking. The present results are in line with previous demonstrations that schedule-induced drinking can be further increased by giving extra food contingent upon licking (Reberg, 1980) or by increasing its associability (Patterson & Boakes, 2012).…”
Section: Discussionsupporting
confidence: 82%
“…The operant contingency helped to develop scheduleinduced drinking under environmental conditions (food frequency) that, by themselves, did not induce that much licking, and the degree of contingency established between licking and food delivery determined the level of acquisition of scheduleinduced drinking. The present results are in line with previous demonstrations that schedule-induced drinking can be further increased by giving extra food contingent upon licking (Reberg, 1980) or by increasing its associability (Patterson & Boakes, 2012).…”
Section: Discussionsupporting
confidence: 82%
“…Schedule-induced or adjunctive behavior therefore shares many characteristics with conventionally defined operant behavior. Reberg (1980) has provided further evidence for this argument by demonstrating that schedule-induced drinking is sensitive to both positive and negative contingencies. Reberg found that drinking increased when licks produced extra food and decreased when extra food was dependent on not licking.…”
Section: Discussionmentioning
confidence: 94%
“…As we detailed in the introduction, ample evidence is now showing that the rate of schedule-induced drinking is sensitive to environmental consequences programmed in relation to the rats' licking, in a way similar to rats' lever pressing being reinforced by food (Bond, Blackman, & Scruton, 1973;Pellón & Blackman, 1987;Reberg, 1980). Furthermore, the variables related to food that have been shown to affect adjunctive behavior also serve to modulate the effects of environmental consequences on licking.…”
Section: Discussionmentioning
confidence: 99%